Politics in the news: Do campaigns matter? A comparison of political news during election periods and routine periods in Flanders (Belgium) - van Aelst, Peter and De Swert, Knut (COMM, 2009)
Abstract Can an election campaign be considered a normal time period, or is it a very exceptional episode in the way the media look at political actors and issues? This is the central question of this article. We claim that during campaigns (political) journalists work under different (legal) conditions and are confronted with politicians and parties that are more active than ever, and with a public that pays more attention to who and how politics is presented. This general claim is made concrete in several hypotheses that are tested on the basis of a large dataset of Flemish news broadcasts between 2003 and 2006. Our results confirm that campaign periods strongly influence the amount, style and actors of the (political) news in Belgium (Flanders).
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tLjIwMDkuMDEx